The Role of The Village Government in the Economic Development of Fisherman Communities in Pulau Harapan Village - Hasdinawati Hasdinawati; Ernawati Ernawati; Abd. Wahid (Jurnal Ad'ministrare, 2021)
Pulau Harapan Village which is one of the villages in the Pulau Sembilan District area. most of the population work as fishermen. This study aims to determine the role of the village government in the economic development of fishermen communities in Pulau Harapan Village, Pulau Sembilan subdistrict. The research method used is descriptive qualitative research. Data collection is observation, interviews with resource persons, namely the Head of the Harapan Island Village, the Secretary of the Pulau Harapan Village, the Tohoh community and the Harapan Island Fisherman Community. Meanwhile, data analysis includes: collecting data, reducing data, assessing data (grouping primary and secondary data), and interpreting data, which is done by critically analyzing the collected data and finally arriving at a conclusion. The results of the study conclude that the Village Government in the Economic Development of the Fishermen Community in Pulau Harapan Village, Pulau Sembilan Subdistrict has not played a sufficient role, especially in realizing and developing production centers, processing industry centers, access to village transportation, building community agribusiness, building business facilities/business centers in rural areas as well as in developing the information and communication technology community